In vitro Activity of Rambutan Binjai (Nephelium lappaceum) Peel Extract from Indonesia to Methicillin-Resistant Staphylococcus aureus (MRSA) - Rostinawati, Tina; Tjitraresmi, Ami; Wisnuputri, Myra Vania (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) is the most common bacteria causing nosocomial infections with high levels of resistance to available antibiotics. So, it is necessary to search for new compounds to solve this problem. Various studies showed antibacterial activity of rambutan peel but for Rambutan Binjai peel extract that are from Indonesia has never been studied against the MRSA. This study aims to determine the antibacterial activity, the value of minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) using agar diffusion method. The concentration of rambutan peel ethanol extract at as much as 62.5 mg/ml showed the inhibitory diameter i.e 21.3 ± 2.4 mm. MIC and MBC were in the same range, which was between 0.98 (mg/ml) to 1.95 (mg/ml). The activity strength of tetracycline against the extract was at 1:50. This revealed that Rambutan Binjai peel extract had great potency as antibacterial agent to MRSA. Dhaka Univ. J. Pharm. Sci. 17(2): 197-203, 2018 (December)